Methods of Activating the Professional Role of the Social Worker in the Medical Sector: An Applied Study on Social Workers in Government Hospitals in Jeddah - Al-Qarni, Abdullah Abdulrahman; Al-Omari, Abdulrahman Abdullah (Journal of Humanities & Social Sciences, 2024)
The study investigates strategies to enhance the professional role of social workers in the medical sector, focusing on social workers in government hospitals in Jeddah Governorate. It examines the current responsibilities of social workers, including patient and family coordination, therapeutic team collaboration, and engagement with the local community, while also exploring the anticipated roles within the medical setting. Employing a social survey methodology, the research surveyed 45 social workers in government hospitals in Jeddah Governorate. Data collection utilized a questionnaire as the primary instrument. Findings revealed that social workers actively contribute to patient care by bolstering self-confidence and providing insights to the therapeutic team regarding patients' life circumstances and environmental influences on health. Additionally, social workers engage with the local community by directing families to relevant support organizations. The study identified an expected role for social workers in fostering understanding and cooperation within the healthcare team. Challenges hindering the full realization of social workers' professional roles in government hospitals were also identified, such as societal misconceptions about their functions. Recommendations include raising awareness about the role of medical social workers through media campaigns and promoting educational programs to enhance public understanding of the social work profession in healthcare.
Keywords: Social worker; medical sector; professional role; activating methods; applied study; government hospitals; Jeddah